2019
DOI: 10.1016/j.chemosphere.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Where has the pollution gone? A survey of organic contaminants in Ho Chi Minh city / Saigon River (Vietnam) bed sediments

Abstract: A wide range of persistent organic chemicals, including polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs), some insecticides, as well as polybrominated diphenyl ethers (PBDEs) and some perfluoroalkyl substances (PFASs) were analyzed in 17 bed sediments collected along the Saigon River and at adjacent canal mouths from upstream to downstream in Ho Chi Minh City (Vietnam). Concentrations were rather low for PAHs, as well as for legacy PCBs and dichloro-diphenyl-trichlorethane and metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…As mentioned above, dredging of the urban canals can explain the high removal of P from the system, sediment being much richer in P in canals (Strady et al, 2017). This conclusion is in line with the observations made by Babut et al (2019) on the disappearance of organic pollutants in the Saigon River.…”
Section: Phosphorus Budgetsupporting
confidence: 88%
See 1 more Smart Citation
“…As mentioned above, dredging of the urban canals can explain the high removal of P from the system, sediment being much richer in P in canals (Strady et al, 2017). This conclusion is in line with the observations made by Babut et al (2019) on the disappearance of organic pollutants in the Saigon River.…”
Section: Phosphorus Budgetsupporting
confidence: 88%
“…H C M C is the largest city in Vietnam and one of the most dynamic in the world (World Economic Forum News, January 2017). Because of urban sprawl and the lack of wastewaters treatments, the quality of the water is deteriorating, which endangers the resource as well as the human activities that depend on it (Babut et al, 2019;Nguyen, Le, Bui, Phan, & Visvanathan, 2011;Strady et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The same trend was observed with Total P in waters. This may be related to the flushing of sediment with high P content from urban canals of HCMC during the wet season; a similar hypothesis of high flushing in the beginning of the wet season was recently proposed by Babut et al (2019). It is also shown that during the dry season P was largely taken up by algae, especially between distance − 40 and − 10 km where Chl-a concentrations increased up to 150 μg L − 1 (Fig.…”
Section: Impact Of Hcmc On Pconcentrationssupporting
confidence: 74%
“…Mangrove river network acts as a unique gate for water outlet from Ho Chi Minh City to the South China Sea. Industrial activities, economic developments and rapid population growth are inducing high pressure on water and sediment quality of the adjacent river, the Sai Gon River (Babut et al 2019, Strady et al 2017. Strady et al (2017) stated that the main rivers and canals in the city were moderately contaminated by major metal(oid)s. Recently, Thanh-Nho et al (2018) highlighted that metals can be transferred over long distance from upstream to the mangrove forest, and that elevated inputs of metals in the estuary were the result of enhanced runoff and soil leaching during the monsoon season.…”
Section: Introductionmentioning
confidence: 99%